1999
DOI: 10.2170/jjphysiol.49.175
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Potentiation by Endothelin-1 Involves Protein Kinase C-.DELTA. Activity in the Porcine Coronary Artery.

Abstract: The relationship between potentiation of serotonin (5-hydroxytryptamine, 5-HT)-induced contraction by endothelin-1 (ET-1) and the activity of protein kinase C (PKC) was examined in the porcine coronary artery. Low concentrations (30-100 pM) of ET-1 selectively potentiated the 5-HT-induced contraction 1.5 to 2 times over the control without any additional increase in myosin light-chain phosphorylation. The potentiation was attenuated by PKC down-regulation caused by phorbol 12-myristate 13-acetate. By Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…6: A -C). In addition, positive staining for PKCδ and PKCε, which have been suggested to be involved in vascular contraction (14,15), was also observed (Fig. 6: D and E).…”
Section: Immunohistochemistry For Pkc Isoformsmentioning
confidence: 78%
“…6: A -C). In addition, positive staining for PKCδ and PKCε, which have been suggested to be involved in vascular contraction (14,15), was also observed (Fig. 6: D and E).…”
Section: Immunohistochemistry For Pkc Isoformsmentioning
confidence: 78%
“…22 We reported that ␣-, ␤ 1 -, ␦, and -isoforms are expressed in the porcine coronary artery. 22 Coronary segments from the spastic and control sites were dissected and cut into rings approximately 4 mm in length. Western blotting for PKC isoforms was performed.…”
Section: Western Blot Analysis For Membrane Translocation Of Pkc Isofmentioning
confidence: 93%
“…Western blotting for PKC isoforms was performed. 22 As a control, one ring was frozen after incubation in PSS, and as an activated preparation, another ring stimulated with serotonin (1 mol/L) was frozen 5 minutes after exposure to the monoanine. These segments were minced with scissors into small pieces in ice-cold buffer, homogenized with a Polytron on ice, and then centrifuged at 100 000g for 30 minutes at 4°C.…”
Section: Western Blot Analysis For Membrane Translocation Of Pkc Isofmentioning
confidence: 99%
See 2 more Smart Citations